2010
DOI: 10.1002/aoc.1654
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Dependent conjugate addition of arylboronic acids to α,β‐unsaturated enones catalyzed by a reusable palladium(II)/cationic 2,2′‐bipyridyl system in water under air

Abstract: A reusable Pd(NH 3 ) 2 Cl 2 /cationic 2,2 -bipyridyl system for the catalysis of the conjugate addition of arylboronic acids to α,β-unsaturated enones in water under air was developed. Addition of arylboronic acids to both cyclic and acyclic enones progressed smoothly, providing the products in good to high yields, the best result being obtained when HBF 4 was used to adjust the pH value to 1.0. After the reaction, the residual aqueous solution could be reused several times, making the reaction greener and red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…We found that the palladium-catalyzed conjugate addition of arylboronic acids to chromones and 4-quinolones delivered tertiary stereocenters in high yield and ee across multiple heterocyclic scaffolds with a wide range of arylboronic acids (Table ). While chromones , and 4-quinolones have been successfully employed in rhodium-catalyzed conjugate addition, to our knowledge, these are the first examples of metal-catalyzed asymmetric conjugate additions to chromones and 4-quinolones using either palladium catalysis or arylboronic acid nucleophiles …”
Section: Heterocyclic Acceptorsmentioning
confidence: 99%
“…We found that the palladium-catalyzed conjugate addition of arylboronic acids to chromones and 4-quinolones delivered tertiary stereocenters in high yield and ee across multiple heterocyclic scaffolds with a wide range of arylboronic acids (Table ). While chromones , and 4-quinolones have been successfully employed in rhodium-catalyzed conjugate addition, to our knowledge, these are the first examples of metal-catalyzed asymmetric conjugate additions to chromones and 4-quinolones using either palladium catalysis or arylboronic acid nucleophiles …”
Section: Heterocyclic Acceptorsmentioning
confidence: 99%
“…We recently reported that cationic 2,2′-bipyridyl is an excellent ligand to bring PdCl 2 (NH 3 ) 2 into the aqueous phase, in order to efficiently perform several carbon–carbon bond-formation reactions, and the residual aqueous solution can be reused for the next run [58,59,60,61,62,63]. As part of our continuing efforts in the development of water-soluble and reusable catalytic systems for carbon–carbon bond-forming reactions, we report, herein, on a reusable PdCl 2 (NH 3 ) 2 /cationic 2,2′-bipyridyl catalytic system, which can be applied for Stille coupling of aryl halides with organostannanes in water under aerobic conditions, in the presence of NaHCO 3 as a base.…”
Section: Introductionmentioning
confidence: 99%